2018
DOI: 10.1130/g45142.1
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric scaling relationships in submarine channel–lobe systems

Abstract: Morphometric analysis of submarine fan systems, the largest sedimentary deposits on Earth, demonstrates scaling relationships between genetically related channels and lobeshaped bodies (LBs) deposited beyond the channel terminus, providing insight into the architectural development of these systems. Compiling dimensional data from depositional systems that cover a range of sediment supply characteristics, tectonic settings, and geographic locations enables investigation into global trends in depositional morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…The channels extending westward from the West Mariana Ridge and from the Anatahan segment of the Mariana backarc also become wider (as much as 3-5 km wide) as they transition out onto the sedimented plain. Measured relationships plotted in Pettinga et al (2018) suggest that the Mariana-scale channels could easily produce lobes ranging up to 100 m thick like those we describe at Site U1438 (Fig. 4).…”
Section: Insights From Modern Analoguessupporting
confidence: 58%
See 1 more Smart Citation
“…The channels extending westward from the West Mariana Ridge and from the Anatahan segment of the Mariana backarc also become wider (as much as 3-5 km wide) as they transition out onto the sedimented plain. Measured relationships plotted in Pettinga et al (2018) suggest that the Mariana-scale channels could easily produce lobes ranging up to 100 m thick like those we describe at Site U1438 (Fig. 4).…”
Section: Insights From Modern Analoguessupporting
confidence: 58%
“…In the modern Mariana backarc, west of Anatahan Island (Chadwick et al, 2005) and the West Mariana Ridge (Gardner, 2010), the quality of bathymetric data decreases, so we cannot rule out the presence of depositional lobes in these settings. Several studies have amassed statistics on lobe-channel relationships for deep-sea fan systems from around the globe that allow for prediction of lobe size and thickness based on channel width (e.g., Pettinga et al, 2018). The channels extending westward from the West Mariana Ridge and from the Anatahan segment of the Mariana backarc also become wider (as much as 3-5 km wide) as they transition out onto the sedimented plain.…”
Section: Insights From Modern Analoguesmentioning
confidence: 99%
“…We do not, however, include channels in the quantitative analysis of natural data presented below, which focuses exclusively on the lobe-shaped bodies. The dimensions of channels have recently been analysed in relation to the dimensions of their concomitant lobes (Pettinga et al 2018), and the dimensions we have used in the models are compatible with the analysis of Pettinga et al…”
Section: Parameterisation Approach and Parameter Definitionsmentioning
confidence: 92%
“…However, due to its simplicity, this scheme provides less information about sedimentary facies, sedimentary structures, and other characteristics useful for inferring depositional environment and dimensions of architectural elements (Cf. Mutti and Normark, 1987;Deptuck et al, 2008;Pettinga et al, 2018;Shumaker et al, 2018). We tested the number of lithology classes using unsupervized machine-learning techniques (e.g., k-means clustering) of the CCL data, and found that five classes is approaching the upper limit of appropriate number of clusters when comparing the silhouette scores.…”
Section: Labeling Of Core Data-lithologymentioning
confidence: 99%